MENGENAL BUDAYA HUKUM DARI PERSPEKTIF PLURALISME HUKUM - Devrayno (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2017)
Law is a social arena associated with humans, human beings as social beings are always associated with other human beings in a social life, no social life in society then there is no law. The law servers to regulate the relationships between people, the plurality of these social relations will affect the existence of law. In other words not all existing social structures will be able to follow the legal system. An undeniable that Indonsia is a country that has a diversity of tribal, religions, language and culture including law. In a society of course apply several legal system, such as the enactment of costomary law in local indigenous communities, in addition it also applies the law of religion and state law. This diversity is also known as legal pluralism.